Virus replication kinetics and pathogenesis of infection with H7N9 influenza virus in isogenic guinea pigs upon intratracheal inoculation. Issue 49 (8th December 2015) - Wiersma, Lidewij C.M.; Kreijtz, Joost H.C.M.; Vogelzang-van Trierum, Stella E.; van Amerongen, Geert; van Run, Peter; Ladwig, Mechtild; Banneke, Stefanie; Schaefer, Hubert; Fouchier, Ron A.M.; Kuiken, Thijs; Osterhaus, Albert D.M.E.; Rimmelzwaan, Guus F.
Highlights: Guinea pigs are susceptible to unadapted human and avian influenza viruses. Influenza A/H7N9 virus is an avian virus first isolated from humans in 2013. A/H7N9 virus replicated to high titers in the entire respiratory tract of guinea pigs. Infection caused rhinitis, tracheitis and bronchointerstitial pneumonia. Peak of viral excretion was at day 2 and continued until 7 days post-inoculation. Abstract: Since 2013, avian influenza viruses of subtype H7N9 have been transmitted from poultry to humans in China and caused severe disease. Concerns persist over the pandemic potential of this virus and further understanding of immunity and transmission is required. The isogenic guinea pig model uniquely would allow for investigation into both. Eighteen female isogenic guinea pigs 12–16 weeks were inoculated intratracheally with either A/H7N9 virus ( n = 12) or PBS ( n = 6) and sacrificed on days 2 and 7 post-inoculation. Nasal and pharyngeal swabs were taken daily to assess viral replication kinetics and necropsies were performed to study pathogenesis. All animals showed peak virus titers in nasal secretions at day 2 post-inoculation and by day 7 post-inoculation infectious virus titers had decreased to just above detectable levels. At day 2, high virus titers were found in nasal turbinates and lungs and moderate titers in trachea and cerebrum. At day 7, infectious virus was detected in the nasal turbinates only. Histology showed moderate to severe inflammation in the entire respiratory tract and immunohistochemistry (IHC) demonstrated large numbers of viral antigen positive cells in the nasal epithelium at day 2 and fewer at day 7 post-inoculation. A moderate number of IHC positive cells was observed in the bronchi(oli) and alveoli at day 2 only. This study indicates that isogenic guinea pigs are a promising model to further study immunity to and transmission of H7N9 influenza virus.